Characterization and Evaluation of Silver-Nanoparticle-Incorporated in Composite Graphite Aiming at their Application in Biosensors - Santos,V. M. (2017)
Abstract Biosensors based on nanomaterial composites have been investigated for their potential to function as high sensitivity signal response devices. In the present study, we report the fabrication of silver nanoparticles (AgNPs) on a graphite epoxy composite electrode (GEC) and mixed with the polyaniline (a conductive emeraldine salt form polymer) composite electrode (AgNPs/PANI/GEC), in order to compare the performance of the generated electrochemical response signals. Cyclic voltammetry tests were conducted to compare the quality and intensity of signals from the different prepared electrodes. Tests for the AgNPs/PANI/GEC electrodes were made with and without the enzymes alcohol oxidase and horseradish peroxidase immobilized on the composite surface. The prepared AgNPs/PANI/GEC nanocomposite was evaluated by thermal analysis. Scanning electron microscopy images and EDX were obtained for characterization of the electrode surface morphology. Square wave voltammetry techniques were then employed for ethanol analysis with the AOX/HRP/AgNPs/PANI/GEC biosensor achieving good results in a range of 0.37M to 0.65 M.